CO2 capture performance of gluconic acid-modified limestone-dolomite mixtures under realistic conditions - Wang, Ke; Gu, Feng; Clough, Peter T.; Zhao, Pengfei; Anthony, Edward J. (American Chemical Society, 2019)
Calcium Looping (CaL) technology has become one of the most attractive ways to capture CO2 from fossil fuel power plants. However, with increasing numbers of cyclic reactions, the CO2 capture capacity rapidly decreases. To address this shortcoming, limestone-dolomite mixtures modified by gluconic acid were explored to prepare highly effective, MgO-stabilized, CaO sorbents that exhibited a high and stable CO2 capture capacity over multiple cycles. The sorbents were all tested over 10 carbonation-calcination cycles and were performed under realistic CaL conditions (calcination in a high CO2 concentration). The results of this research have demonstrated that the inhomogeneous composition that occurs between CaO and MgO - caused by the small CaO crystallite size, porous texture, nanosheet (~100 nm thick) morphology - provides sufficient void space for the volume expansion during carbonation to mitigate the effects of repeated cycle sintering and retain structural stability. A MgO content as low as 10 mol% was able to ensure a superior CO2 capture performance with a fast carbonation rate, high CO2 carrying capacities and remarkable stability. Furthermore, these sorbents retained a conversion (above 90%) over multiple cycles following a recarbonation step